2020
DOI: 10.2174/1570162x17666191128101426
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Pretreatment HIV Drug Resistance and Genetic Transmission Network Analysis Among HIV Patients in a High Drug-Use Area of Southwest China

Abstract: Background: Pretreatment drug resistance (PDR) poses an increasing threat to the success of antiretroviral treatment (ART) programs in China. We aimed to conduct a survey of PDR among HIV patients in an area in Southwest China with extensive drug trafficking. Methods: Consecutive cross-sectional surveys were conducted in Liangshan Prefecture of Sichuan Province from 2009 to 2018 based on the WHO-recommended method. PDR was identified by testing pol region sequences with the Stanford HIVdb algorithm (version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 69 publications
5
11
1
Order By: Relevance
“…In this study, PDR did not lead to an increase in the clustering rate, as did the ndings in 13 provinces or cities in China (include high and moderate prevalence regions) [24], Liangshan Prefecture in Sichuan [23] and Shijiazhuang in Hebei [32]. Studies have suggested that the transmission capacity of resistant strains is lower than that of non-resistant strains [33,34].…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In this study, PDR did not lead to an increase in the clustering rate, as did the ndings in 13 provinces or cities in China (include high and moderate prevalence regions) [24], Liangshan Prefecture in Sichuan [23] and Shijiazhuang in Hebei [32]. Studies have suggested that the transmission capacity of resistant strains is lower than that of non-resistant strains [33,34].…”
Section: Discussionsupporting
confidence: 51%
“…From 2014 to 2020, the overall prevalence of PDR had no downward trend in Qinzhou, Guangxi. Similarly, PDR rates are on the rise in the provinces with the most severe HIV epidemic such as Guangxi in China, similar to Dehong of Yunnan (3.48 to 9.48%) [22] and Liangshan of Sichuan (4.1 to 12.2%) [23,24] from 2009 to 2017. In addition, the most common mutations of NNRTIs were E138A, K103N, and V179D mutations in this study, which was consistent with the study in a nationwide pilot survey of people with HIV/AIDS not receiving ART [24].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, the prevalence of PDR also displayed regional specificity. The prevalence detected in western Yunnan appeared lower than those reported in China, such as 17.4% in Shanghai and 9.9% in Liangshan Prefecture of Sichuan Province [11, 31].…”
Section: Discussionmentioning
confidence: 91%
“…In Liangshan Yi autonomous prefecture located in Southwest China, there are four neighboring key counties, Butuo, Zhaojue, Yuexi and Meigu, which are areas most severely affected by HIV, with a high HIV prevalence exceeding 1% ( 11 ). According to consecutive cross-sectional surveys conducted in Liangshan Prefecture from 2009 to 2018, the major circulating HIV subtype is CRF07_BC, which infected more than 90% of HIV cases in the area ( 12 ).…”
Section: Introductionmentioning
confidence: 99%